Toxicity Test of Turmeric Extract on Wader Fish (Rasbora sp.) Embryogenesis Activity: Uji Toksisitas Ekstrak Kunyit terhadap Aktivitas Embriogenesis Ikan Wader (Rasbora sp.) - Septriani, Nur Indah; Adha, Muhammad Nurul Fathoni; Sa'diyah, Maftuhatus; Septiani, Chelsy Ammara; Amaliah, Meinawa; Bagus, Tsaqifa Suhayra Emery; Natania, Soen Eliora Valerie; Prasetyaningrum, Enjang Sekaryati (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2025)
Turmeric (Curcuma longa) is a medicinal plant containing active compounds, mainly curcumin, which may affect fish embryonic development, an essential stage for species survival. A previous study reported that exposure to chlorpyrifos affected the embryonic development of the wader pari fish Rasbora lateristriata, confirming its suitability as a local model for embryotoxicity testing. Based on this evidence, the present study evaluated the potential toxic effects of turmeric extract during the early stages of embryo development. Toxicity was assessed using turmeric extract concentrations of 50 ppm and 100 ppm in wader fish (Rasbora sp.). The methods included turmeric solution preparation, broodstock selection and spawning, egg collection, treatment grouping, and embryo observation at 0, 24, 48, and 72 hours. Observed parameters were pigmentation, mortality rate, and embryonic heart rate. The results showed that turmeric extract at both 50 ppm and 100 ppm exhibited toxic effects on Rasbora sp. embryos, especially on pigmentation. Higher curcumin concentrations were associated with lower pigmentation levels. Embryo mortality reached 11.1% at 50 ppm and 5.56% at 100 ppm, caused by embryotoxic effects that disrupted embryonic development and induced egg coagulation. Heart rate was slightly lower than the control group, indicating curcumin’s influence on cardiac activity and cellular signaling pathways.